"It's not my business": Exploring heteronormativity in young people's discourses about lesbian, gay, bisexual, transgender, and queer issues and their implications for youth health and wellbeing. (January 2019) - Ng, Cara KY; Haines-Saah, Rebecca J; Knight, Rodney E; Shoveller, Jean A; Johnson, Joy L
In Canada, the issue of creating safe and inclusive school environments for lesbian, gay, bisexual, transgender, and queer students has been in the spotlight. Several researchers and advocates have pointed out the positive effects of lesbian, gay, bisexual, transgender, and queer-positive policy frameworks on the health and wellbeing of all young people. In this article, we take a critical approach to analyzing narrative findings from qualitative interviews conducted with youth in three communities in British Columbia, Canada: "the North, " Vancouver, and Abbotsford. Using a Foucauldian Discourse Analytic Approach and Butler's concept of Citationality, our analysis suggested that although explicit homophobia was largely absent from youth discussions, young people discursively constructed lesbian, gay, bisexual, transgender, and queer identities and "communities" in ways that reified heteronormativity. Youth made references to sociopolitical discourses of libertarianism and liberalism and to homonormative stereotypes regarding gay masculinity. A few young people also alluded to egalitarian, queer-positive discourses, which appeared to interrogate structures of heteronormativity. Since studies suggest a connection between the existence of institutional supports for lesbian, gay, bisexual, transgender, and queer students in schools and their mental and physical wellbeing, we conclude by considering the limitations and possibilities of these sociopolitical discourses in the struggle for sexual and gender equity, and how they might help frame future health-related, anti-homophobia policy frameworks in educational settings.